STRATEGI PEMERINTAH INDONESIADALAM MEWUJUDKAN KEAMANAN MARITIM MELALUI KEBIJAKANPENENGGELAMAN KAPAL SECARA TERBUKA (2014-2017) - Santoso, Syarifurohmat Pratama; Dewi, Ratih Kumala; Suwecawangsa, Adi (DIKSHI (DISKUSI ILMIAH KOMUNITAS HUBUNGAN INTERNASIONAL), 2018)
ABSTRACT The purpose of this study was to determine the strategy of the Government of Indonesia in realizing maritime sovereignty through the sinking of the fishing boats openly from 2014 to 2017. This research is a descriptive qualitative research with the object of research, namely the Government of Indonesia policy. The data were collected by interviewing five informants from the Ministry of Maritime Affairs and Fisheries and the Ministry of Foreign Affairs. In addition, data are also supported by conducting documentary data collection and data search techniques online. The collected data is then analyzed using rational actor models and maritime security concept. Furthermore, the results of the analysis of this study are presented in narrative form. The results showed that the sinking of the fishing boats by the Indonesian Government had a positive impact in realizing Nawacita of President Joko Widodo. Keywords: Maritime Sovereignty, Nawacita, Sinking of The Fishing Boats